A biodiversidade bentônica em lagoa marginal ao rio Paranapanema na zona de sua desembocadura, na represa de Jurumirim - Souza Davanso, Rosemary Cristina [UNESP]; Henry, Raoul [UNESP] (Universidade Estadual de Maringa, 2006)
Coqueiral lake is a marginal lake located at the southeast São Paulo State, in the mouth zone of the Paranapanema river into Jurumirim Reservoir and it has high connectivity with the Paranapaneina river. This work aimed to verify the benthic biodiversity in areas of the lake bottom. 18 sampling sites in the lake were selected, including shallow and deep areas. The samples were taken every three months during one year. Physical and chemical water variables (level, transparency, dissolved oxygen, pH, and electric conductivity) were analyzed. Sediment samples were picked up in triplicate for fauna and abiotic factors analysis (granulometric composition and sediment organic content), using Petersen dredge. The material was sorted out and analyzed under stereoscopic microscope. Counting and identification of the organisms were accomplished and diversity, relative abundance, taxonomic richness and dominance index were calculated. The analysis revealed a fauna with low species diversity and, with Chironomidae and Ephemeroptera dominance. Ephemeroptera, Campsurus, dominated in the hottest period and with low lake depth. Organisms' distribution had as main factors depth, transparency, pH, and water temperature. In the comparison between shallow and deep areas, a small density of organism in the deep regions was observed.
The benthic biodiversity in a lake marginal to the Paranapanema river in its mouth zone into Jurumirim reservoir
Keywords: Benthic; Biodiversity; Coqueiral lake; Jurumirim reservoir; Paranapanema river; organic compound; water; aquatic fauna; benthos; biodiversity; chemical analysis; Chironomidae; electric conductivity; ephemeral plant; factorial analysis; lake; nonhuman; pH measurement; reservoir; river; stereomicroscopy; taxonomy; water analysis; water temperature; Campsurus; Ephemeroptera